Morphological description and evolutionary significance of 300 ka hominin facial bones from Hualongdong, China. Issue 161 (December 2021) - Wu, Xiujie; Pei, Shuwen; Cai, Yanjun; Tong, Haowen; Xing, Song; Jashashvili, Tea; Carlson, Kristian J.; Liu, Wu
Abstract: Late Middle Pleistocene hominins in Africa displaying key modern morphologies by 315 ka are claimed as the earliest Homo sapiens . Evolutionary relationships among East Asian hominins appear complex due to a growing fossil record of late Middle Pleistocene hominins from the region, reflecting mosaic morphologies that contribute to a lack of consensus on when and how the transition to modern humans transpired. Newly discovered 300 ka hominin fossils from Hualongdong, China, provide further evidence to clarify these relationships in the region. In this study, facial morphology of the juvenile partial cranium (HLD 6) is described and qualitatively and quantitatively compared with that of other key Early, Middle, and Late Pleistocene hominins from East Asia, Africa, West Asia, and Europe and with a sample of modern humans. Qualitatively, facial morphology of HLD 6 resembles that of Early and Middle Pleistocene hominins from Zhoukoudian, Nanjing, Dali, and Jinniushan in China, as well as others from Java, Africa, and Europe in some of these features (e.g., supraorbital and malar regions), and Late Pleistocene hominins and modern humans from East Asia, Africa, and Europe in other features (e.g., weak prognathism, flat face and features in nasal and hard plate regions). Comparisons of HLD 6 measurements to group means and multivariate analyses support close affinities of HLD 6 to Late Pleistocene hominins and modern humans. Expression of a mosaic morphological pattern in the HLD 6 facial skeleton further complicates evolutionary interpretations of regional morphological diversity in East Asia. The prevalence of modern features in HLD 6 suggests that the hominin population to which HLD 6 belonged may represent the earliest pre-modern humans in East Asia. Thus, the transition from archaic to modern morphology in East Asian hominins may have occurred at least by 300 ka, which is 80, 000 to 100, 000 years earlier than previously recognized.